Reuse of spent FCC of Dung Quat refinery for cracking wasted cooking oil in liquid phase - Nhu Mai, Tran Thi; Cong, Tran Chi; Manh, Nguyen Van; Bac, Luu Van; Phuong Ly, Giang Thi; Duong, Quach Vien (Vietnam Journal of Chemistry, 2016)
Applications of pretreated spent FCC catalyst in wasted cooking oils cracking were investigated. The spent catalyst was obtained from commercial FCC unit in Dung Quat refinery. The spent FCC catalyst was removing heavy metals by reflux with 5 % concentration solution of enthanedioic acid by magnetic stirring for 5 hours at 75 oC. The obtained results showed that 56% Fe and 30 % Ni were removed. Treated spent FCC catalyst was used in cracking wasted cooking oils in liquid phase at 370 oC, 400 oC and 420 oC for 45 minutes with rate of stirring being 400 rpm. At 400 oC liquid and gas products yield was higher than at 370 oC (82 % and 12 % in comparison with 80 % and 10 %), respectively, as a consequence, unconverted products at 400 oC were smaller than at 370 oC (2.5 % versus 6.3 %). The GC-MS results showed that the obtained products are mainly straight chain alkanes as green diesel. Keywords. Spent FCC, regenerated FCC, green diesel, catalytic cracking.